2021
DOI: 10.1002/mren.202100001
|View full text |Cite
|
Sign up to set email alerts
|

Novel Protocol for Resole Phenol Formaldehyde Resins Synthesis with Tubular Reactor and Characterization

Abstract: A novel strategy has been established, in the laboratory scale, for the generation of the popular thermosetting resin phenol formaldehyde (PF; resole), through a continuous process using a tubular reactor, which is usually developed in the commercial scale through a batch process. A refractive index technique is employed to evaluate the optimum residence time within the tubular reactor to obtain a commercial grade equivalent of PF resin. The unreacted free formaldehyde level has been found to be very low in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In order to validate the applicability of the different model, five different types of PF resoles were synthesized according to the previous literature. 24,25 The formulation and intrinsic properties of resultant PF resole are given in Table 1. Among them, four samples were synthesized through a continuous process while a resole was made through a batch process.…”
Section: Methodsmentioning
confidence: 99%
“…In order to validate the applicability of the different model, five different types of PF resoles were synthesized according to the previous literature. 24,25 The formulation and intrinsic properties of resultant PF resole are given in Table 1. Among them, four samples were synthesized through a continuous process while a resole was made through a batch process.…”
Section: Methodsmentioning
confidence: 99%
“…[24] The gelation time, which refers to the time required for the resin to transform into a three-dimensional cross-linked structure, is an indication of the curing rate and molecular reactivity of the resins. [17,25] Compared to RR, it was observed that the gel times of RR modified with phenylboronic acid decreased with increasing PBA content and free formaldehyde content. A shorter gel time implies that the cross-linking reactions of the resin occur more rapidly.…”
Section: Gelation Time Free Formaldehyde Content and Viscositymentioning
confidence: 98%
“…To determine the total solid content, ≈2 g of the resin sample was weighed and placed in an oven at 378 K for 3 h. After 3 h, the sample was removed from the oven and allowed to cool to room temperature and reweighed. [2,17] Each resin sample was analyzed four times, and the mean value was used to calculate the total solid content using Equation (2) below Total solid content ð%Þ ¼…”
Section: Total Solid Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Because it is an outstanding flame retardant with good adhesion, high heat resistance, excellent mechanical properties, and straightforward processability, phenolic formaldehyde (PF) resin has been extensively used in a number of applications, including coatings, construction, transportation, electronics, and the automotive and aerospace industries. However, its intrinsically low electrical conductivity and high brittleness have limited its widespread use in other fields. Thus, in recent years, electrically conductive polymer composites have attracted considerable attention due to their lightweight, corrosion resistance, and easy processing.…”
Section: Introductionmentioning
confidence: 99%